Pelaksanaan Pembinaan Pendidikan Karakter Pada Sekolah Penyelenggara Pendidikan Inklusi di SDN 131/IV Kota Jambi - Elfia, Delisa; Sofwan, Muhammad; Budiono, Hendra (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2022)
The purpose of this study was to describe the process of implementing character education for inclusive education providers at SDN 131/IV Jambi City, the research approach used was qualitative research with phenomenological research. The research data is in the form of a description of the implementation of character education in inclusive schools at SDN 131/IV Jambi City. The research subjects were classroom teachers, shadow teachers and school principals. The research instruments used were observation guidelines, interview guidelines and documentation. The results of the study indicate that the development of character education in inclusive schools is carried out through learning, example, strengthening, habituation, as for the implementation, namely: 1) Teachers inculcate integrated character values ​​through learning materials, 2) Teachers provide examples of contextual character values, 3) Teachers use active learning, 4) The teacher shows good attitudes and behavior to students, 5) There is a slogan that contains character values, 7) The teacher gives appreciation to students who do good, 8) Cooperation with Shadow teachers, and parents 10) There are activities daily, weekly and monthly routines, 11) The teacher carries out spontaneous activities, 12) There are several programmed activities